Microphase Separation of a PS-b-PFS Block Copolymer via Solvent Annealing: Effect of Solvent, Substrate, and Exposure Time on Morphology - Colm T. O’Mahony; Dipu Borah; Michael A. Morris (International Journal of Polymer Science)
Block copolymer (BCP) lithography makes use of the microphase separation properties of BCPs to pattern ordered nanoscale features over large areas. This work presents the microphase separation of an asymmetric polystyrene-block-poly(ferrocenyl dimethylsilane) (PS-b-PFS) BCP that allows ordered arrays of nanostructures to be formed by spin casting PS-b-PFS on substrates and subsequent solvent annealing. The effects of the solvent annealing conditions on self-assembly and structural stability are discussed.